A Static Fluid Sphere with Non Zero Spin Density: Solutions and Calculations for a Static Conformal Fluid Sphere (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper provides solutions of E - C. field equations for a static conformlly that fluid sphere by taking a suitable relations between Metric potentials pressure, density and spin density have been also calculated.